Social media crises in the organization: exploring management strategies through cases from France and Brazil - Lambret, Clémence Vignal (2016)
The aim of this Master’s thesis has been to shed light on the response strategies that organizations are implementing when facing a crisis created on or amplified by social media. Since the development of social media in the late 1990s, the interplay between the online and the offline spheres has become more complex, and characterized by dynamics of a new magnitude, as exemplified by the wave of 'Twitter' Revolutions or the Wikileaks scandal in the mid 2000s, where online behaviors deeply affected an offline reality. The corporate world does not escape to this worldwide phenomenon, and there are more and more examples of organizational reputations destroyed by social media 'fireballs'. As such, this research aims to investigate, through the analysis of six recent cases of corporate crises (2013-2015) from France and Brazil, different strategies currently in use in order to identify examples of good and bad practices for companies to adopt or avoid when facing a social media crisis. The first part of this research is dedicated to a review of the literature on crisis management and social media. From that review, we were able to design a matrix model, the Social Media Crisis Management Matrix, with which we analyzed the response strategies of the six companies we selected. This model allows the conceptualization of social media crises in a multidimensional matrix built to allow the choice, according to four parameters, of the most efficient (that is: which will limit the reputational damage) response strategy. Attribution of responsibility for the crisis to the company by stakeholders, the origin of the crisis (internal or external), the degree of reputational threat, and the emotions conveyed online by stakeholders help companies determining whether to adopt a defensive response, or an accommodative response. The results of the analysis suggest that social media crises are rather manichean objects for they are, unlike their traditional offline counterparts, characterized by emotional involvement and irrationality, and cannot be dealt with traditionally. Thus analyzing the emotions of stakeholders proved to be, in these cases, an accurate thermometer of the seriousness of the crisis, and as such, a better rudder to follow when selecting a response strategy. Consequently, in the cases, companies minimized their reputational damage when responding to their stakeholders in an accommodative way, regardless of the 'objective' situation, which might be a change of paradigm in crisis management.